Two New Species of Free-living Marine Nematodes (Nematoda: Axonolaimidae and Tripyloididae) from the Coast of Antarctica - Shimada, D.; Suzuki, A. C.; Tsujimoto, M.; Imura, S.; Kakui, K. (Species Diversity, 2021)
Two new species of free-living marine nematodes, Odontophora odontophoroides sp. nov. and Parabathylaimus jare sp. nov., are described from the coastal sand of Langhovde, Lützow-Holm Bay, Dronning Maud Land, Antarctica. Odontophora odontophoroides sp. nov. is the only species in Odontophora Bütschli, 1874 that has bicuspidate odontia. Odontophora odontophoroides sp. nov. is similar to species in Odontophoroides Boucher and Helléouët, 1977 and Synodontium Cobb, 1920 in having bicuspidate odontia, but differs in having a didelphic reproductive system in females. Parabathylaimus jare sp. nov. differs from congeners in the unjointed inner labial and cephalic sensilla, the outer labial sensilla three-jointed in males and two-jointed in females, the position of the amphids, the shorter spicules, and the conical tail without long subterminal setae. Modified generic diagnoses and keys to species are included for Odontophora and Parabathylaimus De Coninck and Schuurmans Stekhoven, 1933. A new combination, Parabathylaimus arthropappus (Wieser and Hopper, 1967) comb. nov., is established.